Substituent effects on the photolysis of methyl 2-carboxylate substituted aliphatic 2H-azirines - Gómez-Zavaglia, Andrea (2007)
In this study, the UV induced photochemical reactions of two 2H-azirines - methyl 2-chloro-3-methyl-2H-azirine-2-carboxylate (MCMAC) and methyl 3-methyl-2H-azirine-2-carboxylate (MMAC) - isolated in argon matrices are compared. For both compounds, irradiation with [lambda] > 235 nm led to observation of two primary photoprocesses: (a) CC bond cleavage, with production of nitrile ylides (P1-type products), and (b) CN bond cleavage, with production of methylated ketene imines (P2-type products). However, subsequent photoprocesses were found to be different in the two cases. In MCMAC, both primary photoproducts were shown to undergo further reactions: P1-type products decarboxylate, giving [(1-chloroethylidene)imino]ethanide, which bears a CN+C- group (P3-type product); P2-type products decarbonylate, yielding a substituted ylidene methanamine (P4-type product). In MMAC, only P2-type primary photoproducts appeared to react, undergoing decarbonylation or decarboxylation (both reactions leading to P4-type products), whereas P1-type products were found to be non-reactive. The non-observation of any secondary photoproduct resulting from photolysis of P1-MMAC revealed the higher photostability of this species when compared with the corresponding photoproduct obtained from MCMAC.